Frequency of frailty and its association with cognitive status and survival in older Chileans - Albala C; Lera L; Sanchez H; Angel B; Márquez C; Arroyo P; Fuentes P (Clinical Interventions in Aging, 2017)
Cecilia Albala,1 Lydia Lera,1 Hugo Sanchez,1 Barbara Angel,1 Carlos Márquez,1 Patricia Arroyo,2 Patricio Fuentes2 1Public Health Nutrition Unit, Institute of Nutrition and Food Technology (INTA), University of Chile, 2Faculty of Medicine, Clinical Hospital, University of Chile, Santiago, Chile Background: Age-associated brain physiologic decline and reduced mobility are key elements of increased age-associated vulnerability.Objective: To study the frequency of frailty phenotype and its association with mental health and survival in older Chileans.Methods: Follow-up of ALEXANDROS cohorts designed to study disability associated with obesity in community-dwelling people 60 years and older living in Santiago, Chile. At baseline, 2,098 (67% women) of 2,372 participants were identified as having the frailty phenotype: weak handgrip dynamometry, unintentional weight loss, fatigue/exhaustion, five chair-stands/slow walking speed and difficulty walking (low physical activity). After 10–15 years, 1,298 people were evaluated and 373 had died. Information regarding deaths was available for the whole sample.Results: The prevalence of frailty at baseline (≥3 criteria) in the whole sample was 13.9% (women 16.4%; men 8.7%) and the pre-frailty prevalence (1–2 criteria) was 63.8% (65.0% vs 61.4%), respectively. Frailty was associated with cognitive impairment (frail 48.1%; pre-frail 21.7%; nonfrail 20.5%, P<0.001) and depression (frail 55.1%; pre-frail 27.3%; nonfrail 18.8%, P<0.001). Logistic regression models for frailty adjusted for sex and age showed a strong association between frailty and mild cognitive impairment (MCI) (odds ratio [OR] =3.93; 95% CI: 1.41–10.92). Furthermore, an important association was found for depression and frailty (OR =2.36; 95% CI 1.82–3.06). Age- and sex-adjusted hazard ratios (HRs) for death showed an increased risk with increasing frailty: pre-frail HR =1.56 (95% CI: 1.07–2.29), frail HR =1.91 (95% CI: 1.15–3.19); after adjustment by age and sex, a higher risk of death was observed for people identified as frail (HR =1.56, P=0.014) and pre-frail (HR =1.30, P=0.065). MCI and dementia were also risk factors for death (MCI: HR =1.69, P<0.027; dementia: HR =1.66, P=0.016).Conclusion: Frailty is highly prevalent and strongly associated with cognitive impairment and depression in older Chileans. The risk for death was higher for frail people, but underlying cognitive impairment is a key component of the lower survival rate. Keywords: frailty, cognitive impairment, aging, Chile, depression